(untitled) (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The study was carried out to compare the inhibitory effects between commonly used antibiotics and bee honey samples, so as to correlate the inhibitory effects between bee honey alone and in combination with antibiotics. Methods: This study was carried out between December 2012 to September 2013. A total of one hundred and twenty-two clinical microbiological specimens and five different floral sourced honey samples were collected between December 2012 to September 2013. Twenty-three multi-drug resistant organisms were selected. Then, AST for commonly used antibiotics, honey alone and combination of honey-antibiotics discs was done. The difference in ZOI of antibiotic contrasting with the antibiotics containing honey were statistically analysed to define the synergism. Results: The inhibition due to honey is variable among bacteria types (F=39.17, p<0.05). From means plot, Staphylococcus and Acinetobacter were recognized as highly susceptible bacteria for honey (Χ = 21.1 ± 6.2 mm and Χ = 18.3 ± 3.3 mm respectively) but Acinetobacter species could not show synergism to honey-antibiotic combination. The tested organisms from Enterobacteriaceae family showed effective susceptibility to Chloramphenicol-honey mixture. Imipenem-honey combination and Gentamicin-honey combination showed significant effects against Pseudomonas aeruginosa. Conclusion: Thus, honey can be used in various bacteria-directed infections and found to be effective in various infections. Incorporation of honey in antibiotics like Chloramphenicol, Imipenem, and Gentamicin work better in healing various infection.